Moral Values in Religious Myths of Bantenese Society - Ayatullah Humaeni (Laboratorium Bantenologi UIN Sultan Maulana Hasanuddin Banten, 2018)
Abstract This article discusses moral values in various religious myths spread on several areas of Banten. How Bantenese society undertands and believes in religious myths that spread out and are still maintained from generations to generations becomes one of the main focuses of this article; besides, it also tries to analyze the meaning and functions of religious myths for Bantenese society; and the moral values contained in religious myths of Bantenese society. This article is a field research using ethnographical method based on anthropological perspective. Library research, participant-observation, and depth-interview are methodes used to collect the data. Religious myths are one of Islamic literatures that still survive in Banten up to now. For Bantenese society, religious myths are considered having moral message and moral values. Religious myths, in some cases, also play significant roles and function for Bantenese society because they frequently contain moral values. Hence, many Bantenese people still maintain and transmit these religious myths to the youg generation.